Super Tall Timber: design research for the next generation of natural structure. Issue 1 (2nd January 2017) - Ramage, Michael; Foster, Robert; Smith, Simon; Flanagan, Kevin; Bakker, Ron
Abstract : This research project aspires to make truly tall timber buildings a reality. Through a combination of theoretical design and physical testing this research demonstrates the viability of timber buildings at much greater heights than has previously been possible. By pushing the limits of theoretical designs into the realms of the supertall, sometimes beyond that which is feasible using current materials and construction technologies, this research also sets out the requirements for the next generation of engineered plant-based materials. The research is a collaboration between academics, practising architects and practising structural engineers. The approach is research through design, and design through research. Timber towers are designed well beyond existing heights, and analysed to understand how they stand up and which areas are most critical for further research. By bringing highly regarded architectural and structural designers together with the research capabilities of a leading university, this project creates a precedent-setting model for interdisciplinary engagement within and between the design and research communities. By coupling exemplary design in timber with a university's research capacity, the project represents a real opportunity for transformational change in the design of tall timber buildings. Essential details and connections are determined and 'unknowns' with respect to material and structural performance are identified. A programme of testing to investigate these unknowns and validate the design approaches is carried out at the university. Outcomes of the test programme and new insights are fed back into the design process. The results show that tall timber towers are feasible, with substantial but surmountable questions outstanding. By providing thought provoking yet credible solutions for the design of tall timber buildings and exceeding current limits, the project can inspire the design community to think beyond the status quo and embrace the possibilities offered by timber construction.